Effects of mu-opioid receptor agonists on circulatory responses to simulated haemorrhage in conscious rabbits. - Evans, R. G. (1990)
1. Cardiac output, arterial pressure, heart rate, systemic vascular conductance, respiratory rate and arterial blood PO2 and PCO2 were measured in unanaesthetized rabbits. Haemorrhage was simulated by inflating a cuff placed around the inferior vena cava so that cardiac output fell at a constant rate of about 8% of its resting value per min. 2. The effects of drug treatments on resting haemodynamic and respiratory variables, and on the haemodynamic response to simulated haemorrhage, were tested. The treatments were; 4th ventricular (-)-naloxone HCl (10-100 nmol), 4th ventricular H-Tyr-D-Ala-Gly-MePhe-NH(CH2)2OH (DAMGO; 30-300 pmol), and i.v. morphine sulphate (0.5-5.0 mumol kg-1). The interactions of graded 4th ventricular doses of naloxone (3-100 nmol) with the actions of DAMGO (100-300 pmol) on these responses were also assessed. 3. After sham treatments, the circulatory response to simulated haemorrhage had two phases. During the first compensatory phase, systemic vascular conductance fell, heart rate rose, and mean arterial pressure fell by only about 7 mmHg. A second decompensatory phase supervened when cardiac output had fallen by about 50%. At this point systemic vascular conductance rose abruptly and arterial pressure fell to less than or equal to 40 mmHg. 4. Low 4th ventricular doses of naloxone (10-30 nmol) and DAMGO (30-100 pmol) had no discernible effect on the circulatory response to simulated haemorrhage. Higher doses of naloxone (30-100 nmol) and DAMGO (100-300 pmol) prevented the decompensatory phase. These high doses of naloxone and DAMGO lowered resting heart rate without affecting the other haemodynamic or respiratory variables.(ABSTRACT TRUNCATED AT 250 WORDS)